Potential contribution of virtual histology plaque composition to hemodynamic–morphologic dissociation in patients with non-ST elevation acute coronary syndrome. (6th May 2015) - Hüseyinova, Güneş; Aslanger, Emre; Çakır, Ozan; Atıcı, Adem; Panç, Cafer; Demirkıran, Ahmet; Sürmen, Semih; Sarıkaya, Remzi; Erdoğan, Onur; Gölcük, Ebru; Umman, Sabahattin; Sezer, Murat
Abstract: Objective: Histologic plaque characteristics may influence the hemodynamic effect generated by physiologically significant unstable coronary lesions where plaque content and surface related factors are expected to contribute to the maximum translesional pressure drop. In this study, we aimed to identify local lesion specific virtual histological characteristics that may potentially affect hemodynamic outcome measures. Methods: Forty-eight consecutive patients with non-ST-elevation acute coronary syndrome (NSTEACS) having paired hemodynamic and morphological data were enrolled. A dual sensor guide-wire was used for the assessment of fractional flow reserve (FFR) and stenosis resistance (HSR) in the culprit vessel. Virtual histology intravascular ultrasound imaging was performed after obtaining hemodynamic data. Results: In a hemodynamically significant lesion subset (FFR < 0.75 [ n  = 34]), after controlling for lesion length, MLA and coronary artery compliance, FFR correlated with necrotic core (NC) area ( r  = − 0.423, p  = 0.028) at MLA and NC volume ( r  = − 0.497, p  = 0.008) and dense calcium (DC) volume ( r  = − 0.332, p  = 0.03) across the entire lesion segment. Likewise, NC ( r  = − 0.544, p  = 0.005) and DC ( r  = 0.376, p  = 0.03) areas at MLA and NC ( r  = 0.545, p  = 0.005) and DC ( r  = 0.576, p  = 0.003) volumes across the entire lesion segment were associated with HSR in the hemodynamically significant lesion group (HSR > 0.80 [ n  = 33]). However, no correlation has been observed between intracoronary hemodynamic end-points and plaque components in hemodynamically insignificant lesions. Conclusions: This study demonstrated that for a given coronary stenosis geometry and arterial compliance, plaque composition may influence hemodynamic outcome measures in functionally significant stenoses in patients with NSTEACS.